PENGARUH PEMANASAN MODIFIKASI TERHADAP EFEKTIFITAS PASSING BAWAH BOLAVOLI (STUDI PADA KELAS VIII SMP NEGERI 40 SURABAYA) - UMAR FARUK, IQBAL (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The teaching can be effective if the students will be easy in learning something usefull such as : skill, new experience, score, and how to live compatibally with others. Because of it, the teacher have to know any kind of teaching methods. This research, is applied one of teaching methods that give a signiticant effect to the learning produce, that is teaching methods with give warming modification to the studenst. This research have a purpose to know the effects of warming modification gifts to the effectiveness of volley ball’s under passing teaching to the students of SMP Negeri 40 Surabaya. This research, include in research experment that use Randomized control Group Pretest – Postest research of design. Populate that use in this research is the students of VIII grade SMP Negeri 40 Surabaya which is consists by 8 classes with 291 students. Sample that use in this research is the students of VIII C as a control class who has 37 students, the taking of sample by cluster sampling technique. The effects of volley ball’s under passing teaching with warming modification, proven by the increasing test score of under passing to the wall which is bigger in pretest, posttes in experiment class is 22,19% compare with control class is 12,51%. The conclution is a gift of warming modification have the effects to the volley ball’s teaching effetiveness to the students of VIII grade of SMP Negeri 40 Surabaya. Keywords : teaching effectiveness, warming modification, junior high scoll student, volley ball under passing.